Heat transfer to nanofluids in closed conduits flow / Thenarasu Pakiyanathan - Thenarasu, Pakiyanathan (2021)
Different nanoparticles were synthesized and covalenty or non-covalently functionalized to disperse the nanoparticles properly in different base fluids. Thermo physical properties of the nanofluids were measured in different equipment and the nanofluids were characterized. Heat transfer coefficient, friction losses were analyzed with the variation of concentrations, particle characters, particle types etc. Heat transfer and friction loss properties were then correlated with the particle characters and the variable physical and thermal properties of the nanofluids. Experimental and numerical results were compared for validation of the data and application as reference. The common working fluid in a heat exchanger can be identified as oil, water and ethylene glycerol etc. These fluids exhibit advantages in terms of ease of handling, recycling and disposing. Besides that, it has a low market price. Despite the advantages listed, these fluids exhibited low thermal properties. Moreover, characteristic such as fouling and low total surface energy makes the overall heat transfer performance low resulting in the design of heat exchanger to be larger so that the desired energy can be harnessed for the operations in the time duration. Nanofluid has been identified as a substitute to water and oil as a working fluid in the heat exchanger. There were attempts to incorporate it into the industry. At turbulent fully developed flow in annular passage for TiO2+SiO2/DW and GAGO/DW nanofluids, the friction factor, pressure drops, heat transfer coefficient and Nusselt number at constant heat flux boundary condition were evaluated. The outcomes of the experimental data were compared with those of the base fluids. However, the current findings shown the improved heat exchanger fluids as the nanofluids. They have improved thermo-physical characteristics and heat transfer enhancement, such as about 200 percent improvement in heat transfer coefficient at a low nanoparticle concentration of 0.1wt percent. There was not much extra frictional pressure drop at such a low concentration of nanofluids. Thus the new and environmentally friendly TiO2+SiO2/DW and GAGO/DW nanofluids could be used as highly effective working fluids in a variety of heat transfer applications and specially in the situations when a high heat transfer rate is required